Debacle Obama's War and Jobs and Growth and What we can do now to Regain our future - Norquist, Grover Glenn; Lott, John R (Hoboken John Wiley & Sons Ltd., 2012)
"During the 2008 presidential campaign, Obama promised time after time "a net spending cut" to make government smaller in order to cut the deficit. But the huge increase in government spending and debt, and the resulting higher future taxes will make Am
Keywords: United States -- Economic policy -- 2009- United States -- Economic conditions -- 2009- United States -- Politics and government -- 2009-2017.